Factor Influencing Consumers Preference in Klang Valley Market: A Study of Natural Personal Care Products - Shukri, Sakinah; Azman, Norhidayah Binti; Budiarto, Dekeng Setyo; Sudin, Sabri; Sofiadin, Aidrina (Information Management and Business Review, 2023)
Several research studies have been conducted to investigate the factors that can influence the brand preference of consumers. However, there are very few studies that examine the factors that influence consumers’ brand preference toward personal care products in the Klang Valley of Malaysia. This study was conducted to ascertain the factors that influence consumer brand preference for personal care products in Klang Valley to fill the void. This investigation included 3984 Klang Valley residents who had purchased and have a brand preference toward personal care products as a sample. Quantitative research was conducted by disseminating the devised questionnaire to the targeted number of participants online. 384 valid responses were collected from 450 distributed survey questionnaires and analyzed using SmartsPLS Software. The contribution of this current study will be the reference for marketers who are producing natural personal care products in setting the right strategy to create and maintain their brand preference among customers.